Penerapan Metode FMEA dan FTA untuk Mengurangi Kegagalan pada Weight Feeder 532-WFI Finish Mill 2 di PT. SBI Tuban - Hidayati, Nurul; Kusuma, Gilang Budi; Soleh, Muhamad; Pratiwi, Yuliyanti Dian (Fakultas Teknik Universitas Tulang Bawang, 2026)
The cement industry faces significant challenges in maintaining operational continuity due to auxiliary equipment failures that impact overall productivity. Weight feeder 532-WF1 at Finish Mill 2 PT Solusi Bangun Indonesia Tbk Tuban experienced 9 unplanned shutdown incidents during June-October 2024 with a total duration of 31.57 hours, resulting in production losses of 8,208 tons of cement. This research aims to identify dominant failure modes and analyze root causes through integrated implementation of Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) methodologies. FMEA implementation identified 15 potential failure modes with highest Risk Priority Numbers (RPN) for belt drifting (504), alarm failure (448), and belt damage/rupture (360). FTA analysis revealed 14 basic events as root problems, where mechanical misalignment became the dominant contributor. Implemented improvement strategies included standardization of alignment procedures, component material upgrading, and real-time temperature monitoring implementation. Effectiveness evaluation demonstrated zero breakdown achievement during April-May 2025 period, validating the success of risk analysis-based preventive maintenance approach in enhancing weight feeder system reliability. Keywords: Finish Mill, FMEA, FTA, Weight feeder